Estimation of heritability of susceptibility to infection with Theileria parva in the tick Rhipicephalus appendiculatus - Young, A.S.; Dolan, T.T.; Mwakima, F.N.; Ochanda, H.; Mwaura, S.N.; Njihia, G.N.; Muthoni, M.W.; Dolan, R.B. (Cambridge University Press, 1995)
Heritability of susceptibility to infection with Theileria parva was estimated from full sib families of Rhipicephalus appendiculatus ticks. Male and female ticks of 2 stocks were mated singly. Nineteen full sib families of the Mugufa stock and 17 full sib families of the Kiambu stock were obtained. Nymphar of these families were fed on cattle infected with T. parva so that the ticks became replete on days 16 and 17 after infection when the blood was parasitaemic with intraerythrocytic piroplasms. The T. parva infections were assessed in the resultant adult ticks of each full sib group and the abundance of infection, the number of salivary gland acini infected/tick, was found to be the most useful parameter for analysis. Estimates of heritability of the susceptibility to infection with T. parva for the Kiambu and the Muguga tick stocks were 0.24 and 0.26 respectively. Using only the data from ticks which fed on day 16, the heritability estimates were 0.39 for the Kiambu stock and 0.59 for the Muguga stock. These results-indicate that tick lines of high or low susceptibility for T. parva infection could be produced through selection.